Protein phosphorylation in neurodegeneration: friend or foe? - Tenreiro, Sandra; Eckermann, Katrin; Outeiro, Tiago F. (Frontiers in Molecular Neuroscience, 2014)
Protein misfolding and aggregation is a common hallmark in neurodegenerative disorders, including Alzheimer’s disease (AD), Parkinson’s disease (PD), and fronto-temporal dementia (FTD). In these disorders, the misfolding and aggregation of specific proteins occurs alongside neuronal degeneration in somewhat specific brain areas, depending on the disorder and the stage of the disease. However, we still do not fully understand the mechanisms governing protein aggregation, and whether this constitutes a protective or detrimental process. In PD, alpha-synuclein (aSyn) forms protein aggregates, known as Lewy bodies, and is phosphorylated at serine 129. Other residues have also been shown to be phosphorylated, but the significance of phosphorylation in the biology and pathophysiology of the protein is still controversial. In AD and in FTD, hyperphosphorylation of tau protein causes its misfolding and aggregation. Again, our understanding of the precise consequences of tau phosphorylation in the biology and pathophysiology of the protein is still limited. Through the use of a variety of model organisms and technical approaches, we are now gaining stronger insight into the effects of phosphorylation in the behaviour of these proteins. In this review, we cover recent findings in the field and discuss how targeting phosphorylation events might be used for therapeutic intervention in these devastating diseases of the nervous system.